Postoperative Outcomes and Patient Satisfaction Following Laparoscopic Versus Open Inguinal Hernia Repair: A Comparative Study - Nawaz Ali Dal, Mahak Qureshi, Samar Memon, Ghulam Murtaza, Tanveer Sadiq Ch, Shaheer Azhar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Laparoscopic and open are the two main ways of doing inguinal hernia repair. Laparoscopic repair has advantages including reduced postoperative pain and quicker recovery, however, feasibility, efficacy, and accessibility of this procedure in resource limited settings like Pakistan is not clear. Objective: To compare, evaluate and quantify the postoperative outcomes, complications, recovery time and patient satisfaction between laparoscopic and open inguinal hernia repair at tertiary care setting in Pakistan. Methods: This was a prospective comparative study conducted at three tertiary care hospitals in Pakistan. Eighty adult patients with primary unilateral reducible inguinal hernia were randomly assigned to undergo laparoscopic versus open inguinal hernia repair. Operative time, hospital stay and postoperative complications were the primary outcomes. Other outcomes included pain assessment by the Visual Analog Scale (VAS), return to normal activities, and patient satisfaction. SPSS version 26.0 was used to perform statistical analysis, significance of p < 0.05. Results: Operative time was longer with laparoscopic repair (91.2 ± 14.7 min vs. 57.9 ± 11.5 min, p < 0.001) but shorter with hospital stay (1.1 ± 0.5 days vs. 2.5 ± 1.0 days, p < 0.001). There was significantly lower postoperative pain in the LIHR group (p < 0.001). The total complication rates were lower in the laparoscopic group (7.5 vs. 15.0, p = 0.048). The patients who have undergone laparoscopic repair were found to be more satisfied with the outcome. Conclusion: The postoperative outcomes after laparoscopic inguinal hernia repair are better, such as less pain, less time in hospital and faster recovery. Despite it, in Pakistan its adoption is limited to due to cost and training requirements. Keywords: Inguinal hernia, Laparoscopic repair, Open repair, Postoperative outcomes, Patient satisfaction, minimally invasive surgery, Pakistan.